Sex differences in cerebral palsy incidence and functional ability: a total population study. (12th April 2013) - Chounti, A; Hägglund, G; Wagner, P; Westbom, L
Abstract Aim To describe gender difference in a total population of children with cerebral palsy (CP), related to subtype, gross and fine motor function, and to compare CP incidence trends in girls and boys. Methods All 590 children with CP born in southern Sweden 1990–2005 were included. CP subtype was classified according to the Surveillance of Cerebral Palsy in Europe, gross motor function according to Gross Motor Function Classification System (GMFCS) and manual ability according to Manual Ability Classification System (MACS). Trends in CP incidence by birth year were analysed using Poisson regression modelling. Results There was a male predominance in all levels of GMFCS except level II, in all levels of MACS and in all CP subtypes except ataxic CP. There was no statistically significant difference between males and females regarding gross motor function or manual ability. The CP incidence trends in boys compared with girls did not change during the period 1990–2005. Conclusion No equalization was detected in the incidence of CP between girls and boys during recent years in this total population. We could not confirm any consistent sex difference in motor function levels. Male sex is a risk factor for CP.